TRIAL OF FIVE SEED SOURCES OF SENGON (Paraserianthes falcataria L. Forberg) WITH COMPOST TREATMENT - Aris Sudomo; M. Yamin Mile (Jurnal Pemuliaan Tanaman Hutan, 2007)
Trying out sengon seed source by giving the compost was conducted in private forest area of Sukamulih Village, Sariwangi Sub-District,Tasikmalaya Dsistrict. This research used Split Random Design with five main plots of sengon seed source (Subang,Ciamis,Candiroto,Wamena, and Kediri) and five kinds of compost dose as the sub Plots (0 kg/plant, 1 kg/plant, 2 kg/plant,3 kg/plant and 4 kg/plant) so that there were 25 treatment combinations. The research shows the best diameter growth and significantly different friom other provenances,wich is 3.91 cm. The plant with 2 kg compost as its basic fertilizer treatment gives 3.46 cm as its best diameter. This data is insignificant with the diameter growth of plant with 3 kg and 4 kg compost treatments. Sengon with no compost (0 kg/plant) shows the worst diameter, which is 2.04 cm. Seed source interaction with the compost has a significant result on height growth of sengon. The sengon seed from Subang with 2 kg compost/plant shows the best height growth, which is 3.27 cm.